PROSES PENGOMPOSAN TANDAN KOSONG KELAPA SAWIT (TKKS): ANALISIS FISIK DAN KENAMPAKAN ORGANISME - Edhi Sarwono; Dwi Ermawati Rahayu; Weldy Dziya Millati; Sariyadi Sariyadi (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
Oil Palm Empty Fruit Bunches (OPEFB) are among the processed palm oil's waste products. A tone of processed fresh oil palm fruit bunches produces 22-23% of OPEFB. Using OPEFB as mulch for the gate takes a long to decompose and triggers rhinoceros beetles as palm oil pests. Therefore, this study determined OPEFB composting process and the emerging organisms. The composting method involved open windrow with material mixture variation without leachate and EM4 (Effective microorganisms 4), with additional EM4, leachate, and leachate and EM4. OPEFB was chopped to 2-4cm, and the pieces were stacked with dimensions of (120cm x 80cm x 100cm). The results showed that adding activators in the composting process did not affect the organism’s appearance. Bioactivators visually affect the texture, smell, and material color. Furthermore, temperature, pH, and humidity had a similar trend in the composting process. The organisms that emerged from the composting process include maggots, ants, fungi, and millipedes